PREDIKTOR DISFUNGSI EREKSI PADA PENDERITA DIABETES TIPE 2 DI POLIKLINIK PENYAKIT DALAM RS SANGLAH DENPASAR - Ratna Saraswat, Made; Sanjaya, Dwija; Suastika, Ketut (journal of internal medicine; Vol. 9, No. 2 Mei 2008, 2012)
Erectile dysfunction (ED) is a commonly reported condition among men with diabetes, however little is known about the predictive factors associated with diabetic ED. To examine the predictors related to ED among type 2 diabetes outpatient, a consecutive cross sectional study at Internal Medicine Outpatient Clinic, Sanglah Hospital was conducted, enrolled 137 type 2 diabetes men aged between 35 ? 77 years old. We found 79.5% of type 2 diabetics with ED. Erectile function score was significantly correlated with other component of International Index of Erectile Function 15 (IIEF 15) including orgasmic function (r=0.622, p<0.001), sexual desire (r=0.782, p<0.001), intercourse satisfaction (r=0.911, p<0.001), and overall satisfaction (r=0.842, p<0.001). Erectile function was also correlated with age (r=0.315, p<0.001). Chi square analysis among diabetic complication, ED were significantly higher among patient with albuminuria/proteinuria (p=0.025, prevalence ratio 7.43 (95% IC 0.95 ? 58.15). Other factors such as duration of diabetes, central obesity, cigarette smoking, alcoholism, diabetic control (HbA1C and lipid profile), diabetic complications, and hypertension were not significantly correlated with ED. ED were high among type 2 diabetics and erectile function were correlated with orgasmic function, sexual desire, intercourse satisfaction, and overall satisfaction. ED also correlated with age and albuminuri/proteinuria but not with other predictors.
Keywords: erectile disfunction, type 2 diabetes.